(untitled) (Theatrum historiae, 2013)
Alexander Nicolaevich, the heir of the Russian imperial throne, later the Emperor Alexander II (ruled 1855–1881), made a long journey through Europe in 1838–1839. Article, based primarily on the correspondence between Alexander and his father Nicholas I, is focused on this journey as a part of the prince’s preparation for his future reign, in the context of the other journeys of the Romanov family and Russian nobles through Europe.